A facile synthesis of nano-layer structured g-C3N4 with efficient organic degradation and hydrogen evolution using a MDN energetic material as the starting precursor. (8th February 2019) - Wang, Min; Li, Zhilin; Tian, Lihua; Xie, Yuanhua; Han, Jin; Liu, Tingyu; Jin, Chongyue; Wu, Zengmin
Abstract: The construction of a high-performance g-C3 N4 photocatalyst through a facile and green synthesis method remains a great challenge for H2 production and organic pollutants degradation. In this work, we developed a nano-layer structured g-C3 N4 (NL-CN) photocatalyst with a 230 m 2 /g surface area via the thermal polymerization method using melaminium dinitrate (MDN), which is one of the more energetic materials, as the precursor. The energy coming from the drastic decomposition of nitrate anions in MDN caused the thick layers of bulk CN to be exfoliated to produce many much-thinner nano-layers when at 500 °C for 2 h, which obviously elevated the surface area of the g-C3 N4 . The resultant NL-CN displays a superior visible-light H2 -generation and rhodamine B (RhB) photodegradation efficiency (λ > 420 nm) compared to those of bulk g-C3 N4 (CN) prepared through heating melamine because of the nano-layered structures, which lead to higher specific surface areas, a rapid charge transfer efficiency and a higher redox potential. These results demonstrate that the utilization of MDN as a starting material provides a new opportunity for the facile and green synthesis of high-efficiency nanostructured g-C3 N4 photocatalysts with lower energy consumption and environmental pollution levels. Highlights: The nano-layer structure g-C3 N4 was successfully prepared through heating MDN. NL-CN sample's specific surface area can reach to be about 230 m 2 /g. NL-CN exhibited an elevated performance of H2 generation and organic pollutant degradation. The higher activity is related to higher surface areas and stronger redox potential.